Physical and mechanical properties of three layer particleboard from oil palm frond / Norfazlina Zainal, Siti Noorbaini Sarmin and Jamaludin Kasim - Zainal, Norfazlina; Sarmin, Siti Noorbaini; Kasim, Jamaludin (2011)
This study was undertaken to determine the properties of three layered particleboard from oil palm frond (OPF) with different ratio resin content and particle sizes. Four different ratio of resin content; 12:10:12, 12:8:12, 10:10:10 and 10:8:10 were used with particle size for core; 2mm and face/back; 1 mm. Urea Formaldehyde (UF) was used as a binder with/without wax addition. The target density was 500kg/m3. The properties of bending strength, internal bonding (IB), thickness swelling (TS) and water absorption (WA) were evaluated base on JIS standard. From the result, it shown that MOR and MOE value were perform better with particleboard using ratio 12:8:12 bonded with UF without wax. The IB strength was parallel with bending strength except for board using 12:10:12 ratio bonded using UF with addition of wax. TS and WA rate showed lower in particleboard using resin contain with ratio 12:8:12. In conclusion, the ratio of resin contain within the layered affected the properties of particleboard manufactured from OPF.